IPTEKS PENYUSUNAN LAPORAN REALISASI ANGGARAN PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN C MANADO - Mamuaja, Kirana Falerina (Universitas Sam Ratulangi, 2020)
Budget Realization Report is one component of the government financial statements that presents information about the realization and budget reporting entities in an equal manner for a certain period. Budget Realization Reports can provide information to report users about the indication of the acquisition and use of economic resources that have been carried out efficiently, effectively, accountably, and have been carried out in accordance with the budget and in accordance with statutory regulations. Customs and Excise has duties and functions that are closely related to the management of state finances. Customs and Excise manages state finances and carries out state revenue through import duties and excise. As a government agency that deals directly with export and import activities, Customs and Excise continues to strive to create various facilities in order to boost the pace of the Indonesian economy.